Otimização de procedimentos para execução de obras públicas em pequenos municípios - Silva, Haroldo Guedes Xavier da (2012)
The process of Public Works execution demands knowledge of the laws, concepts, definitions and standards techniques relating to the subject. Small towns, besides the fact of being in need of specialized technical staff for the necessary activities, are also deficient in the use of tools and procedures to optimize the process to obtain a final product satisfaction. The present work has as main objective to assist professionals engaged in the development of activities related to execution of a Public Works. The methodology used to achieve this objective was a literary research of legislation, guides, manuals, booklets, books, monographs and other documents with themes related to this work. With this research, it was possible to expose and detail various issues within the context discussed, among which the principles of public administration, law of tenders and contracts, control agencies and resources to towns. Furthermore, it was possible to list the main steps by which a Public Works must pass from its original intent and need, through feasibility studies, preparation of technical documents, bidding procedures, execution, monitoring, receipt of the work, until its effective use. The compilation of all this information culminates in a final product, a step by step of the stages of a Public Works, succinctly and objectively, for verification and conference of the attendance of key aspects and activities required throughout the process.